Intelligent AI-Powered Cybersecurity Architecture on AWS Cloud for Financial and Healthcare Systems (International Journal of Engineering & Extended Technologies Research (IJEETR), 2023)
The rapid adoption of cloud computing in financial and healthcare sectors has significantly increased operational efficiency and data-driven decision-making. However, this shift also exposes these industries to sophisticated cyber threats, including data breaches, ransomware, fraud, and insider attacks. To address these challenges, this paper proposes an Intelligent AI-Powered Cybersecurity Architecture on AWS Cloud for Financial and Healthcare Systems. The proposed architecture integrates cloud-native services with artificial intelligence and machine learning models to enable proactive threat detection, risk prediction, and automated response mechanisms. It leverages heterogeneous data sources such as network traffic, user behavior logs, and transaction records to identify anomalies and predict potential cyber risks. Security measures, including encryption, access control, and compliance monitoring, ensure adherence to regulatory standards such as HIPAA, PCI-DSS, and GDPR. Experimental evaluation demonstrates enhanced detection accuracy, reduced response time, and robust protection against evolving threats across multi-cloud environments. This framework provides a scalable, intelligent, and secure solution for managing cybersecurity risks in financial and healthcare systems.
Keywords: AI; Cybersecurity; AWS Cloud; Machine Learning; Financial Systems; Healthcare Systems; Risk Prediction